The implementation of Project Based Learning Models in Improving Social Interaction Ability on Children Aged 5-6 Years in Dharma Wanita Bumimulyo Kindergarten Batangan District Pati Regency - Apriyanti, Kiki; Diana, Diana (BELIA: Early Childhood Education Papers, 2016)
Social interaction ability is a part of the social development which is important to be developed early, with good social interaction ability, children will be able to cooperate, sharing, respect and help other people. The stimulation of the child's social interaction ability can be done by implementing an innocative and appropriate learning models, one of them is a project-based learning model.The purpose of this research is to determine the difference the social interaction ability on children aged 5-6 years be examined the project-based learning model implementation in Dharma Wanita Bumimulyo Kindergarten Batangan District Pati Regency. This research is using pre-experimental one-group pretest-posttest types design. The sampling technique using purposive sampling with Dharma Wanita Bumimulyo Kindergarten as the experimental group. Based on the hypothesis testing results of this study, obtained a value of tcount amounting -22.148 with sig value (2-tailed) 0.000 <0.05, which means that there is a significant differences between the pretest and posttest. So, Ha is accepted or there is a difference between before and after treatment with project-based learning model in the experimental group.